Implikasi Serial Squid Game 2 terhadap Diplomasi Soft Power Korea Selatan di Amerika Serikat Tahun 2024-2025 - Eka Wahyu Muria Ningsih; Roisatun Nadhiroh; Ashifa Dhea Andriani; Doan Widhiandono (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research examines the impact and influence of Squid Game 2 on American public perceptions of South Korea, as well as how the series has become an instrument of soft power in bilateral relations between the two countries. This research is based on the increasing influence of South Korean popular culture in the global arena, especially in the entertainment industry that plays a diplomatic role and can shape public perception. The method used is descriptive qualitative with a case study approach. Data was collected using content analysis techniques obtained from various secondary data such as mass media articles, entertainment industry reports, previous research, and audience reviews on social media. The results showed that Squid Game 2 succeeded in increasing the interest and enthusiasm of the American public for South Korean culture, as well as strengthening South Korea's image and position as a global cultural force. The Squid Game 2 series became popular among the American public because of the storyline containing cultural elements, the characters played by well-known actors in South Korea, the long-awaited continuation of the story from the previous season, and the innovative marketing strategy that made fans actively promote the series voluntarily. Thus, in this phenomenon, the Squid Game 2 series became a tool of South Korean diplomacy in the United States through an approach based on the appeal of popular culture, namely the entertainment industry.